1978
DOI: 10.1007/bf00606676
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between serum concentration and pharmacological effect on atrioventricular conduction time of the antiarrhythmic drug propafenone

Abstract: Seven patients with cardiac dysrhythmias received a single, oral, therapeutically effective dose of the antiarrhythmic drug propafenone. The serum levels correlated well with changes in atrioventricular conduction times during the postabsorptive elimination phase (r = 0.8610, p less than 0.001). The mean half-lives of the serum level and the electrocardiographic effect (PQ-time) were 3.6 +/- .2 h and 3.8 +/- 0.6 h, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 4 publications
1
21
0
Order By: Relevance
“…The mean elimination half-life of propafenone in our group of patients is 6 hr, which is considerably longer than the mean half-life of 3.6 hr previously reported. 6 We also found that there was large interindividual variability in elimination half-life (range 2.4 to 11.8 hr). This vanrability was not explained by clinical factors such as age, liver disease, heart failure, or the presence of concomitant medications that could interfere with the elimination of a drug that is highly metabolized.…”
mentioning
confidence: 52%
“…The mean elimination half-life of propafenone in our group of patients is 6 hr, which is considerably longer than the mean half-life of 3.6 hr previously reported. 6 We also found that there was large interindividual variability in elimination half-life (range 2.4 to 11.8 hr). This vanrability was not explained by clinical factors such as age, liver disease, heart failure, or the presence of concomitant medications that could interfere with the elimination of a drug that is highly metabolized.…”
mentioning
confidence: 52%
“…"he samples were shaken for 30 min and centrifuged, and the upper organic phase was transferred to conical tubes and evaporated in a water bath at 40 "C. Propafenone concentrations were measured by the HPLC procedure described by Keller et a1. 12 The Knauer HPLC used was equipped with a Knauer UV detector and a stainlese steel (6 mm i.d. x 25 cm) column, packed with Lichrosorb Si 60.…”
Section: Methodsmentioning
confidence: 99%
“…The wide range of concentrations of propafenone tested (0.037-37.8 jig ml[') includes not only the therapeutic plasma levels (0.5-2 tg ml-': 1.3 x 10-6-5.3 x 10-6M; Keller et al, 1978;Karagueuzian et al, 1983;Conolly et al, 1983), but also the toxic plasma levels of the drug. The doses selected for pretreatment ofanimals were chosen from the results of Dieckmann et al (1981).…”
Section: Discussionmentioning
confidence: 99%
“…In these two series of pretreated animals plasma concentrations of propafenone were measured with a high-pressure liquid chromatographic method as described by Keller et al (1978). This method allowed sufficiently precise determinations of levels down to 1-2 ng ml-'.…”
Section: Experiments In Propafenone-pretreated Animalsmentioning
confidence: 99%